Menneskeverd en utfordring for skole og samfunn - Valen-Sendstad, Ådne; Reite Christensen, Ingrid (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2019)
"Human Worth - A Challenge for School and Society addresses the question of whether all human beings' lives have equal value. To answer, the authors examine how we should understand the value of human life. Human worth and equality are both fundamental principles in education, but there are countless examples of how difficult these concepts can be in actual practice. There is also scant discussion within the school system that touches on our understanding of what human worth in school is. Insofar as school is society's most important vehicle for human learning and development, we view understanding human worth as a challenge our entire society faces. This book is an anthology in nine chapters about human worth in such typically 'humanity-oriented' school subjects as pedagogics, philosophy, social studies, religion, Norwegian, and arts and crafts. The book provides and introduction to defining human worth from a variety of theoretical perspectives, with examples from school and everyday life. The individual chapters pose questions about dignity, equality, inclusion and exclusion, and the resources human beings engage in meeting challenges. "